Contract sex: Decriminalization versus legalization. Issue 1 (2nd December 2021) - Shrage, Laurie
Abstract: Why are sex worker rights groups advocating for decriminalizing sex work, but not for legalizing it? In this paper, I will explain why efforts to decriminalize sex work deserve the same support as efforts to decriminalize abortion, marijuana, or polygamy. Many human rights advocates now recognize that decriminalizing sexual transactions which take place among consenting adults in private, including informally contracting for sexual services, is necessary for protecting our fundamental human and civil rights. Yet decriminalizing individual acts of prostitution opens the door to various kinds of organized and public market activities, and there is little consensus among progressive reformers about how wide this door should be pushed opened. A consensus has been forming, nevertheless, among sex worker rights organizations. These groups generally hold that regulatory restrictions specific to sex work ("legalization"), which limit where and how contracting for sexual services can take place, leads to practices that are punitive toward sex workers in ways similar to criminalization. In this paper, I will consider the arguments for decriminalization and against legalization, and argue that accepting levels of governmental oversight above the norm may be a necessary compromise in order to change policies regarding a controversial activity. Resumen: ¿Por qué los grupos de derechos de las trabajadoras y trabajadores sexuales abogan por la despenalización del trabajo sexual, pero no por su legalización? En este artículo, explicaré por qué los esfuerzos para despenalizar el trabajo sexual merecen el mismo apoyo que los esfuerzos para despenalizar el aborto, la marihuana o la poligamia. Muchos defensores de los derechos humanos reconocen ahora que la despenalización de las transacciones sexuales que tienen lugar entre adultos que consienten en privado, incluida la contratación informal de servicios sexuales, es necesaria para proteger nuestros derechos humanos y civiles fundamentales. Sin embargo, la despenalización de los actos individuales de prostitución abre la puerta a varios tipos de actividades organizadas y del mercado público, y hay poco consenso entre los reformadores progresistas sobre qué tan amplia se debe abrir esta puerta. Sin embargo, se ha estado formando un consenso entre las organizaciones de derechos de las trabajadoras sexuales. Estos grupos generalmente sostienen que las restricciones regulatorias específicas al trabajo sexual ("legalización"), que limitan dónde y cómo se puede realizar la contratación de servicios sexuales, conduce a prácticas que son punitivas para las trabajadoras sexuales de manera similar a la criminalización. En este artículo, consideraré los argumentos a favor de la despenalización y en contra de la legalización, y argumentaré que aceptar niveles de supervisión gubernamental por encima de la norma puede ser un compromiso necesario para cambiar las políticas con respecto a una actividad controvertida. 摘要: 为何性工作者权利团体倡导将性工作去犯罪化, 而不是合法化?本文中, 我将解释为何为性工作去犯罪化所作的努力, 与为堕胎、大麻或多配偶制去犯罪化所作的努力值得一样的支持。许多人权倡导者现在认为, 发生在私下、经同意的成人性交易, 包括非正式性服务合约, 对保护我们的基本人权和民权而言是必要的。不过, 对个体卖淫行为去犯罪化一事为不同类型的有组织活动和公共市场活动敞开大门, 并且就该大门应打开的程度而言, 进步性改革者之间基本不存在共识。尽管如此, 性工作者权利组织之间正在达成一个共识。这些组织一般认为, 性工作的监管限制 ("合法化") 规定了性服务登记的地点和方式, 导致出现一系列针对性工作者的、类似于犯罪化的惩罚性实践。本文中, 我将考量支持去犯罪化的主张和反对合法化的主张, 并且论证认为, 为变革有关争议性活动的政策, 政府监督对规范之外的接受程度可能是一个必要的让步。